The Appropriateness of Cognitive Behavior Therapy to Reduce Adolescent’s Social Media Addiction - Netrawati Netrawati (Universitas Negeri Padang, 2022)
Millennial generation is currently faced with rapid developments and advances in the field of technology and communication. The use of technology can be utilized for a lot of things, such as interacting in social media by sending messages or voice note, calling, listening to music, reading books through digital platform, reserving hotel, online, going online shopping in one time. Social media provides many experiences from psychological perspective with the potential which can cause problematic behavior. The use of social media in society can be termed as a double-edged sword causing negative effects such as, addiction or dependence on social media. Social media addiction is potentially becoming mental health problem for some users accessing excessively without any limit social media addiction is a habit or behavior that gives the feeling of pleasure when accessing the social media account for a long time and feels uncomfortable, angry, or bored if he cannot open the account. CBT is a therapy directing and modifying thoughts, feeling, and action by emphasizing the brain as analysis, decision making, questioning, action, and return decision that are directed at changing for better behavior. Th purpose of the study is to produce counseling module with cognitive behavior therapy setting group approach to reduce practical social media addiction and can be useful for counseling teachers at school. Through counseling with CBT approach, clients are trained to monitor their mindset and identify feelings and situations that can trigger their social media addiction behavior. This study uses ADDIE model development (Analyze, Design, Development, Implementation, and Evaluation), because ADDIE model employs general and systematic basis, the framework is gradual from one part to another. The counseling module for cognitive behavior therapy approach to reduce social media addiction in adolescents is appropriate both in content and appearance. It is ready to be used by counseling teachers at schools.